Ethical dilemma: nursing and use of psychotropic drugs in children and adolescents in the servicio nacional de menores - Ricardo Humberto Pérez Abarca; Jessica Olate Andaur (Universidad de Alicante, 2018)
Objective: Reflect about Nursing and the use of psychoactive drugs in children and adolescents in situations of violation of rights and / or criminal situation, who are in the care of the Servicio Nacional de Menores, in the context of deaths in recent years. Methodology: Analytical-synthetic method; Bibliographical review, comprehensive reading, personal reflection and definition of concepts. Results: There are described the current situation of mental health of children and adolescents, the relationship with the Social Determinants of Health and related ethical perspectives for conflict resolution. Conclusions: The use of psychosocial interventions as the first line of treatment is considered in the reflection, besides the fact that the use of psychoactive drugs, if necessary, should be administered and supervised by professionals according to current regulations.